Could neonatal testosterone replacement prevent alterations induced by prenatal stress in male rats? - Pereira, OCM; Bernardi, M. M.; Gerardin, DCC (Elsevier B.V., 2006)
The present study was designed to examine whether testosterone replacement is able to prevent some effects of maternal restraint stress during the period of brain sexual differentiation - on endocrine system and sexual behavior in male rat descendants. Pregnant rats were exposed to restraint stress for 1 h/day from gestational days 18 to 22. At birth, some male pups from these stressed rats received testosterone propionate. The neonatal testosterone replacement was able to prevent the reduction in anogenital distance at 22 days of age observed in pups from stressed pregnant rats as well as prevents the decrease in testosterone levels during the adulthood of these animals. Testosterone replacement in these males also presented an improvement in sexual performance. In this way, testosterone replacement probably through increasing neonatal level of this hormone was able to prevent the later alterations caused by the prenatal stress during the period of brain sexual differentiation. (c) 2005 Published by Elsevier B.V.
Keywords: prenatal stress; brain sexual differentiation; testosterone; sexual behavior; male rat